2013
DOI: 10.1097/hp.0b013e3182667721
|View full text |Cite
|
Sign up to set email alerts
|

Use of Portable X-ray Fluorescence (PXRF) In Vivo as an Alternative Technique for the Assessment of Iron Levels in Patients With Thalassemia and Hemochromatosis

Abstract: This work investigated the viability of the portable x-ray fluorescence (PXRF) technique as a means of measuring iron levels in patients suffering from thalassemia major (beta-thalassemia) and hereditary hemochromatosis (HH or Haemochromatosis) or other iron-overload conditions. Measurements were conducted at the University Hospital Blood Center and in the Laboratory of Applied Nuclear Physics at the State University of Londrina, Brazil. One thalassemia major patient and four healthy people were grouped. A PXR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Previously, other authors have demonstrated the potential of devices to measure iron levels in vivo by XRF. However, high detection limits meant their research could only focus on assessment in the range from normal to iron overload [22,23]. This work aims to improve the detection limit and provide a faster measurement with a portable device that would measure the iron levels over the entire clinical range from iron deficit anaemia to iron overload.…”
Section: X-ray Fluorescence (Xrf)mentioning
confidence: 99%
“…Previously, other authors have demonstrated the potential of devices to measure iron levels in vivo by XRF. However, high detection limits meant their research could only focus on assessment in the range from normal to iron overload [22,23]. This work aims to improve the detection limit and provide a faster measurement with a portable device that would measure the iron levels over the entire clinical range from iron deficit anaemia to iron overload.…”
Section: X-ray Fluorescence (Xrf)mentioning
confidence: 99%
“…This device is useful in situations where sampling is not allowed, such as in this study. Due to these advantages, XRF analysis has been applied to human tissue . In addition, the equation below indicates that XRF analysis is effective for long half‐life radionuclides: N=T12ln2A, where N is the number of atoms; T 1/2 is the half‐life (s); and A is the radioactivity of the radionuclide (Bq).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these advantages, XRF analysis has been applied to human tissue. [3][4][5] In addition, the equation below indicates that XRF analysis is effective for long half-life radionuclides:…”
Section: Introductionmentioning
confidence: 99%
“…This methodology was first used in medicine for elemental analysis in animal bones and a variety of biological tissues [1517]. In recent years, XRF has been adopted to in vivo studies for quantification of lead [18], iron [19], and iodine [20]. In the last decade, X-ray fluorescence (XRF) tomography was developed as an imaging technique based on XRF quantitative analysis using monochromatic synchrotron X-rays for elemental analysis of small samples [2123].…”
Section: Introductionmentioning
confidence: 99%